Health‐related quality of life after extracorporeal membrane oxygenation: a single centre's experience - Marte Christine Ørbo; Sidsel Fredheim Karlsen; Ellinor Phillips Pedersen; Stig Eggen Hermansen; Per Bjørnerud Rønning; Kathrine Aas Nergaard; Torvind Næsheim; Truls Myrmel (ESC Heart Failure, 2019)
Abstract Aims The aims of this study were to evaluate health‐related quality of life (HRQL) among patients treated with extracorporeal membrane oxygenation (ECMO) in northern Norway over a period of 27 years (1988–2015) and to identify variables related to HRQL. Methods and results A retrospective inquiry of the ECMO registry at the University Hospital of North Norway identified 74 ECMO‐treated patients (mean age 49 years, 65% males). Acute cardiac failure was the dominant indication (58%), and venoarterial ECMO was the dominant mode of treatment (87%). Mortality for discharged patients was recorded on 20 September 2016. Thirty (41%) survivors were identified. Twenty‐three survivors were eligible for the survey and received a set of questionnaires at home. The main outcome measure was HRQL as measured with the 36‐item Short‐Form health survey (SF‐36) (RAND Short Form‐36 v1.2). Other questionnaires covered demographic information, problems with functioning in usual daily activities (such as hobbies, household chores, family, or work), employment status, and psychological distress. The survey was completed by 20 (87%) survivors (mean age = 49 years, 12 men). Indications for ECMO treatment (VA = 90%) had been respiratory failure (25%), cardiac failure (60%), and extracorporeal cardiopulmonary resuscitation (15%). The average time since ECMO treatment was 6.5 years. Seventy‐five percent reported mental HRQL (SF‐36 Mental Component Summary, mean = 43, SD = 5) or physical HRQL (SF‐36 Physical Component Summary, mean = 43, SD = 4.5) within the normal range (T = 50 ± 10) in comparison with age‐matched population data from national norms. Half of the responders reported problems on the SF‐36 subscales general health and role physical. Seventy percent reported problems on the SF‐36 subscale role emotional. All but one responder lived independently without any organized care, and 90% reported no problems related to basic self‐care. Half of those in working age had returned to work after ECMO treatment. Forty percent of the responders reported some degree of restrictions in usual daily activities, problems with mobility (35%), anxiety/depression (35%), or pain/discomfort (55%). Significant univariate associations were observed for poorer HRQL and higher reports of psychological distress, pain, and experiencing restrictions in usual everyday activities. Improved HRQL was significantly related to an extended time since ECMO treatment. Conclusions Our survey indicates an overall positive long‐term HRQL outcome for our ECMO survivors. A subset reported problems with functioning and HRQL. Future research should focus on identification of the survivors at risk for poor recovery who may benefit from rehabilitation interventions.